Skjoldbuler – offer og symbol Ritualer, kosmologi og magt i skandinavisk jernalder - Nielsen, Anni Pind (Kuml, 2013)
Shield bosses – offerings and symbols – Rituals, cosmology and power in Iron Age Scandinavia The South Scandinavian war booty offerings, which date from the Roman and Germanic Iron Ages, contain thousands of weapons and other military objects. Many of these have been intentionally damaged using remarkable force and in strange ways. The focus of this article is on the destruction of weapons and the aim is to reach an understanding of this phenomenon in the light of the social structure in the Iron Age. Of the 32 bronze shield bosses recovered from Illerup Ådal, eight have been broken using the butt of an axe head (figs. 2-4). The axes from Illerup are also quite damaged and it appears as if they have been used to destroy many hundreds of objects. Some of the imprints seen on the bronze shield bosses even match the dimensions of the axe butts (figs. 1 and 5). There appears to be some consistency in the manner in which the shield bosses were damaged even though they belong to two different stages of the offering site. This could result from a fixed ritual method of destroying shield bosses. It is also possible that only a few individuals participated in the destruction of these objects, because the ways in which the shield bosses have been broken are very similar. It is remarkable that the implements used to destroy shield bosses and weapons in the war booty offerings were other weapons. This could be due to a belief in personification of weapons/objects, such that they represented the warriors to whom they had belonged. There is also a peculiar absence of items in the finds from the Illerup site. Many of the axes that must have been used to destroy the shield bosses have not been recovered. In only six instances out of 12 has it been possible to find an axe that matches the dimensions of the distinct square impressions seen on the shield bosses. Other items and fragments are also missing. It is concluded here that the missing objects could have been taken to other locations or given as gifts to princes or warlords, possibly in connection with the creation of alliances. The Early Roman Iron Age was a period of great unrest as new and old elites fought for power. This is why the alliances were so important. As a consequence of this new social and economic organisation, warriors were now employed full time by the elite. It is therefore only natural that war, warrior identity and weapons were also dominant concepts in religious life. This can be seen in the finds recovered from war booty offerings, graves, central places etc. Central places appear to take over the role of religious centres after the war booty offerings ended. Votive activity appears to have become more institutionalised during the period when the war booty sacrifices flourished. Subsequently, this became particularly pronounced and participation may have been reserved for the select few. This reflects the fact that the elite had now established their right to the power and had no longer a need to compete openly. Anni Pind Nielsen Hedensted